PUBLIC OFFICIALS IN THE CIVIL AVIATION FIELD: CONCEPTS AND CLASSIFICATION - Гусар, Ольга Анатоліївна; Кириченко, Вікторія Вячеславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to investigate the issues of civil servants as employees of the law, to propose the author’s definition of the term «public officials in the field of civil aviation» and their classification. Research methods: the study was conducted using a system of general and scientific methods of cognition, which provide an objective analysis of the subject under study. The components of the methodological base are objectivity, value and structural-systemic approaches, a combination of approaches of critical and rational, constructive, comparatively retrospective and logical. Results: public officials Aviation Civil Servants is considered in the context of a collective entity that has a common purpose: providing civil aviation security and providing quality civil aviation services. They carry out continuous professional activities for the purpose of performing public - power functions (corporate or service), which require specific knowledge and act as a link between the state and citizens. Establishing an effective system of government as a key issue for democratic change depends to a large extent on the organization of the public service, the level of professionalism, competence and patriotism of the civil servants who must be responsible for achieving the goal of the reforms. Provision of quality public services, activity and ability of public administration to adequately respond to the challenges of dynamic social transformation, restoring people’s trust in public authorities - these are the tasks facing the public service and indicate the need to change it conceptually, which necessitates the need for scientific research. its organization and analysis of relevant world practice in the context of prospects for its adaptation in Ukraine. The doctrinal development of the problem of civil servants in the field of civil aviation is a new area of ​​science of administrative law. Depending on the policies and activities of civil servants in the field of civil aviation, they can be divided into: 1) aviation security officers (employees of the State Aviation Service of Ukraine, employees of the National Bureau of Investigation of Aviation Events and Incidents with Civil Aircraft; 2) employees, that provide air transportation and their services (airline employees (operators), airport employees, airport employees, maintenance workers tion and maintenance); 3) employees who organizes the use of the airspace of Ukraine (UkSATSE). Discussion: the concept of civil servants in the field of civil aviation, criteria for the classification of civil servants.